The effect of quarterly earnings guidance on share values in corporate acquisitions - Koch, Adam S.; Lefanowicz, Craig E.; Robinson, John R. (Journal of Corporate Finance, 2012)
We investigate whether quarterly earnings guidance by corporate takeover targets is associated with acquisition premiums. Regulators have expressed recurring concerns that quarterly guidance is associated with a misallocation of resources because it encourages management to focus on excessively short-term horizons. If so, firms providing quarterly guidance represent an acquisition opportunity for non-guiding firms because acquired resources can be redeployed towards more productive long-term uses. Based on prior research that finds value created by acquisitions accrues primarily to target shareholders, we predict that an expected increase in value from the termination of guidance will be observed in acquisition premiums. We find that, after controlling for the other determinants of acquisition gains, the premium paid for an acquired corporation is associated with the target's practice of issuing quarterly earnings guidance. Consistent with our prediction, we find that no incremental premium is paid to acquire guiding targets when the bidding firm also provides guidance.